Anteseden Sikap Merek Terhadap Minat Pembelian Smartphone Xiaomi Pada Mahasiswa Perguruan Tinggi Swasta Di Kabupaten Garut - Asep Saepuloh (Jurnal Wacana Ekonomi, 2019)
This study aims to determine the effect of perceived brand value on brand attitude in students, brand trust affects brand attitude, brand pride affects brand attitudes and to analyze the effect of brand attitude on buying interest in the Xiaomi smartphone brand. Data collection using a simple random sample a number of respondents who have been selected. Data were analyzed using the structure equation model (SEM) with the amos 21 program. The validity test of the indicators had a loading factor above 0.5, so all indicators used were said to be valid. This study uses the criteria of goodness of fit and the data must meet the assumptions in normality, outliers, multicollinearity and singularity. The results of the research that have been conducted show that the perception of brand value has a positive influence on brand attitude, so the higher the perception of brand value in the Xiaomi smartphone brand product. Brand trust has a positive influence on brand attitude. Brand pride has a positive influence on brand attitude. Brand attitude affects brand buying interest, so the higher brand attitude towards Xiaomi smartphone brand products found from the research results. Companies must increase consumer brand buying interest in Xiaomi smartphone products, through brand attitude must be improved from the perception of brand value, brand trust and brand pride of Xiaomi Samsung smartphone brand products.